Empirical analysis of turbine and generator efficiency of a pico hydro system. (February 2020) - Safdar, Ibadullah; Sultan, Sara; Raza, Hamza Ahmad; Umer, Muhammad; Ali, Majid
Abstract: In this research, the performance of a pico hydro system is analyzed by determining turbine and generator efficiency. The turbine used is an impulse type while, for power generation, a 3 phase AC permanent magnet alternator is accompanied in the system. Other electrical components are also installed for frequency stabilization to operate the load safely. The effect of flow rate and installation of equipment's i.e. battery and inverter on the turbine and generator efficiency is investigated in this paper. The results obtained from the experiment revealed that the alternator power, pressure, and torque exerted on the alternator shaft entirely depend on water flow rate. The speed of the alternator is also affected after incorporating battery and inverter in a pico hydro system. The optimum permanent magnet alternator efficiency of 48.35% is achieved at a flow rate of 15.4 gpm and afterward, it starts decreasing due to the stator and rotor losses inside the alternator. The turbine efficiency is related to net and jet head and also water and jet velocity and found maximum at 19.7 gpm flow rate.